Extraction of coffee berry borer adults and larvae from fruits - Nardon, Adriana Cristina; Fujihara, Ricardo Toshio; Rosa, Daniel Dias (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to develop a new method for extracting Hypothenemus hampei adults and larvae from coffee (Coffea arabica) fruits. The extractor consists of a set of two plastic containers, with one fit on top of the other: the one on top is used to place the fruits inside and the one on the bottom, as a base to capture adults and larvae. The efficiency of the extractor was compared with that of the dissection method (control). The number of live adults, dead adults, and larvae does not differ significantly between the two evaluated methods. The developed extractor reduces hand labor, is affordable, and is effective in capturing larvae and adults of H. hampei.